Perancangan Rating Tool untuk Evaluasi Green IT di Perguruan Tinggi - Cecep Muhamad Sidik Ramdani; I Made Oka Widyantara (Prosiding SISFOTEK, 2025)
Sustainability issues in information technology are gaining increasing attention as energy consumption, carbon emissions, and environmental impacts from the use of software and digital infrastructure increase. This research aims to develop a Green IT evaluation framework based on a rating tool that is integrated with the principles of the Green Software Foundation (GSF) and COBIT 2019 as an IT governance framework. This approach combines the basic principles of sustainable software evaluation, such as carbon efficiency, energy efficiency, hardware efficiency, networking efficiency, and holistic lifecycle evaluation, with relevant COBIT 2019 objectives, such as resource optimization, managing enterprise architecture, managing quality, and monitoring performance. The results of this integration form an Environmentally Sustainable Computing (ESC) framework that covers four main dimensions: design, deployment, monitoring & refactoring, and governance & policy. Each dimension has assessment indicators with a maturity level scale of 0–5, so it can be used as an evaluation tool for the level of IT sustainability in higher education. This research is expected to be able to provide conceptual and practical contributions in the development of a Green IT rating tool that is applicable in the academic environment.